ARABIC-THE EFFECT OF DIFFERENT EXPRESSIONS OF HADITHS ON THE EXPLANATION OF HADITHS ACCORDING TO IMAM AL-TABARANI "THROUGH HIS BOOK AL-MUJAM AL-AWSAT" - Abdul Samee Jessar; Feth Ur Rehman Gorashi (دی اسکالر)
Praise be to all mighty Allah, Lord of the all things, and prayers and peace be upon His Messenger, our Master, The Mustafa and his family, and his Brothers among The Prophets, and his Companions, and Those who follow him with honestly until Day of Judgment, Imam al-Tabarani is one of the great scholars of Islam and the well-known person in Islamic World, He was the “Musnad Duniyah” Umamah rely on Him about Prophet’s (peace be upon him) Narrations. Al Muajm Al-Awast is most important Book of Hadith especially in ELAL (some hidden reason effect on Hadith), He said: “This is my Soul” its means core of his Knowledge, Subject of This Book collect Poor chain of Narrations, Method of Imam Al Tabrani comment every Hadith, and indicate Tafrud (singular chain or text of narration), or indicate conflict between narrators in the narration. I (Researcher) make title: “The explanation of Imam al-Tabarani by changing the body text in The Al-Mujam al-Awsat”, take some Hadiths form This Book about some words of Hadith changed that can be right and can be wrong, can be same meaning, can be differ to each other, so I explain what kind of changing ?.